Advancements in MXene-polymer composites for high-performance supercapacitor applications. (July 2023) - Abdah, Muhammad Amirul Aizat Mohd; Awan, Hafiz Taimoor Ahmed; Mehar, Maida; Mustafa, Muhammad Norhaffis; Walvekar, Rashmi; Alam, Mir Waqas; Khalid, Mohammad; Umapathi, Reddicherla; Chaudhary, Vishal
Abstract: State-of-the-art energy storage devices have gained much attraction owing to the high demand for electronic appliances, electric vehicles and automobile applications. In this context, supercapacitors are emerging electrochemical energy storage models (EESMs) that have been demonstrated to bridge the gap between capacitors and conventional battery systems based on their distinctively high-power density, first-rate cycle stability, and rapid charge-discharge rate capability. Due to their excellent energy density and mobility, 2D materials are widely utilized to architect electrode materials for supercapacitor applications. MXene, a novel kind of 2D material, has gained tremendous attention due to its exceptional electrochemical attributes imitative from its transition metal nitride/carbide/carbonitride components and metallic electrical conductivity. Despite the excellent results of employing MXenes and their composites in energy storage devices, the restacking nature of MXene layers restricts the penetration of electrolytes and further decreases the utilization of MXene's ion adsorption/desorption sites. As a result, the development of MXene polymer composites offers an innovative approach that inhibits the restacking of MXene sheets and introduces functionalization, thereby enhancing the material's electrochemical performance. This review focuses on MXene and its polymer-based composite materials to architect supercapacitors for energy storage devices. We also summarized the different harnessing techniques of MXene and polymers followed by the various properties, such as structural, electrical, thermal, mechanical, etc. In addition, applications of MXene and polymer materials related to supercapacitors, along with future challenges and outcomes, are also explained comprehensively. Graphical abstract: Unlabelled Image Highlights: Summarized advancements in the MXene-polymer composites for supercapacitor application. Summarized the different harnessing techniques of MXene and polymers. Supercapacitors are emerging electrochemical energy storage models. MXene polymer composites can boosts the electrochemical performances.